Concept and scope of technical measures to trade. (1st January 2019) - Kong, Xiaobang
ABSTRACT: 'Technical Measures to Trade' is a term coined by Chinese scholars and practitioners. It is closely related to the Agreement on Technical Barriers to Trade (TBT Agreement) and the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS Agreement) of the World Trade Organization (WTO), but it is not a WTO term. Chinese scholars and managers also have a different understanding and classification of the concepts and categories of Technical Measures to Trade, which brings difficulties to the research and practice of international and Chinese scholars and also has a negative impact on the transparency of relevant laws and regulations of China.